2021
DOI: 10.1017/gmh.2021.23
|View full text |Cite|
|
Sign up to set email alerts
|

Mental health needs of the COVID-19 patients and staff in the Fangcang shelter hospital: a qualitative research in Wuhan, China

Abstract: BackgroundDuring the COVID-19 pandemic, Fangcang shelter hospitals were opened in Wuhan, China, to isolate and care for patients with mild or moderate symptoms. The patients and staff in the hospitals faced mental health challenges. This paper reports the experiences and mental health needs from them. MethodFollowing the qualitative design, semi-structured interviews were conducted in the EastWest Lake Fangcang Shelter Hospital, Wuhan on March 2020. Data collection and analysis was based on grounded theory. Op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Mental distress among COVID-19 patients, particularly during the early stages of the pandemic, has been widely reported 16 17 37. This study, in support of previous research,18 37 38 revealed that these negative emotions largely stemmed from poor knowledge of the disease, family concerns and the perceived social stigma. Concerning the highly transmissible nature of COVID-19 and absence of targeted therapy,39 patients’ feelings of fear and uncertainty were unsurprising.…”
Section: Discussionsupporting
confidence: 82%
“…Mental distress among COVID-19 patients, particularly during the early stages of the pandemic, has been widely reported 16 17 37. This study, in support of previous research,18 37 38 revealed that these negative emotions largely stemmed from poor knowledge of the disease, family concerns and the perceived social stigma. Concerning the highly transmissible nature of COVID-19 and absence of targeted therapy,39 patients’ feelings of fear and uncertainty were unsurprising.…”
Section: Discussionsupporting
confidence: 82%
“… 8 , 13 , 16 Experiments from some regions have shown that Fangcang shelter hospitals are feasible and do not require a large amount of investment, although further improvements and complete systems are needed in terms of form, regulation, and treatment procedures. 14 , 15 , 17 , 18 The management mode of Shanghai Fangcang shelter hospital has been further optimized and upgraded in the following aspects.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, the WHO estimated that a disaster resulted in diverse mental health problems for 30–50% of the population ( 17 ). Since 30 January 2020, the COVID-19 pandemic has been declared a worldwide public health emergency by the WHO, which was considered an international concern ( 18 ). Numerous studies reported that people who experienced COVID-19 infection were at high risk of having mental health challenges such as anxiety, depression, sleep disorder, and even post-traumatic stress disorder.…”
Section: Discussionmentioning
confidence: 99%